FREE LITERATURE LEARNING DURING THE COVID-19 PANDEMIC - Ninawati Syahrul (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2021)
Indonesia has taken the PISA test since 2000, but the results continue to show a decline. The field of reading is at an alarming level, there is no learning process in schools that is able to improve students' reading abilities. In fact, enjoying reading is a prerequisite to become an effective reader. For that, reading activities must be made as a culture. Reading literary works should be an obligation for students and listed in the curriculum. This study aims to describe and apply the importance of reading literary works using qualitative methods and literature study analysis. The results showed that reading literary/fiction works was more significant in developing students' reading skills than reading other types of texts, such as magazines, non-fiction, newspapers, and comics with the following explanation. First, reading literature/fiction is reading with full appreciation or deep reading. It takes longer than reading other types of text. Second, the most important factor in reading literary/fiction works in improving students' reading skills lies in the process of enjoying the readings that are read so that they can develop students' reading activities. Third, reading literary/fiction works means that students read life so that students will be able to choose or take a (good/bad) attitude in dealing with that life. The Covid-19 pandemic which requires everyone to maintain social distance should be a